IMPLEMENTASI KEBIJAKAN PEMASANGAN PERSONAL IDENTIFIKASI NUMBER BEBAS PARKIR PADA KENDARAAN PEGAWAI NEGERI SIPIL DI KOTA PALU - Ayu, Neneng Gusti (Katalogis, 2016)
This research aims at finding out more about the reason why Palu City Government apply a policy for installing the Personal Identification number of free parking on the Civil servants’ vehicles in Palu perceived of Communications, Resources, Attitudes and Structures Bureaucracy aspect. The method used is descriptive qualitative research methods and data collection was conducted using observation, interviews, and documentation. The informants selection technique was implemented purposively consisting of 7 people. The results shows that Policy Implementation on Installation of Personal Identification Number of Free Parking on Civil Servants’ Vehicle in Palu has not been run optimally, because the resource, disposition and bureaucratic structures aspects have not been provided well.